The Influence of Job Satisfaction and Work Motivation on the Performance of Employees in the Assembling Department at PT Adis Dimension Footwear, Tangerang Regency - Firmansyah, Arya; Yulandari, Sri; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine: (1) the partial effect of satisfaction on employee performance; (2) the partial effect of work motivation on employee performance; (3) the simultaneous effect of satisfaction and work motivation on employee performance. This study uses a quantitative descriptive method, which describes variables as they are, supported by numerical data generated from actual conditions. The population in this study was all employees in the Assembly division at PT. Adis Dimension Footwear Balaraja-Tangerang. The research sample consisted of 84 respondents. This study used a saturated sampling technique due to the small population size; therefore, the sample in this study used the entire population of 84 employees as respondents. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used multiple linear regression analysis with SPSS 26. Data validity was obtained through a partial t-test and a simultaneous F-test. The results of this study indicate that (1) partially, satisfaction significantly influences the performance of employees in the Assembly division at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (3.112>1.990) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, work motivation significantly influences the performance of employees in the Assembling section at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (4.413>1.990) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, work satisfaction and motivation significantly influence the performance of employees in the Assembling section at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by F count> F table (32.253>3.11) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that the variables of work satisfaction and work motivation, both partially and simultaneously, have a significant influence on the performance of employees in the Assembling division at PT. Adis Dimension Footwear Balaraja-Tangerang.